Documented records of Gaidropsarus granti (Osteichthyes: Lotidae) in the Adriatic Sea and review of its Mediterranean occurrences : is it a native fish or a newly established one? - Bello, Giambattista (Array, 2018)
Gaidropsarus granti (Osteichthyes: Lotidae) is a rare fish that was recorded for the first time in the Mediterranean Sea in 1989. The Mediterranean records have been documented for the Ligurian Sea, the Levant Sea close to Rhodes, off the Sardinian coasts and for the northern Ionian Sea south of the Straits of Messina. Additional reports referred its presence in the Alboran Sea, in the southern Adriatic Sea and west of Malta, though without any additional information. The present paper reports the occurrence of G. granti in the Adriatic Sea (eastern Mediterranean) thanks to the examination of eight specimens collected in its south-western part, between February 1997 and October 2017. Six of them had been trawled at depths from 190 to 290 m, mainly in a channel within coral banks, while two were caught by hook at 420 m depth on coral banks. Their total length ranged from 21.0 to 32.3 cm. Four dissected individuals were adult, three males and one female. The stomach of two individuals contained only galatheid shrimps of the genus Munida, some of which were identified as M. rutllanti. According to interviews with fishermen based in the area where G.granti specimens were trawled, this conspicuous fish was unknown to them until the 1997 captures. Afterwards, it became well known to all of them, because few specimens are presently caught every once in a while. It is discussed whether G. granti is a native Mediterranean species or a fish that entered this sea a few decades ago. Both hypotheses have some support. The autochthonous origin hypothesis is mainly based on both G. granti distribution throughout the Mediterranean and its unavailability to old fishing gear uncapable of fishing on deep, rough grounds. The contrasting allochthonous hypothesis is backed by the total lack of Mediterranean records prior to 1989 coupled with its quite long larval pelagic phase.